2018
DOI: 10.1017/pan.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Citation Patterns across Political Science and Social Science Methodology Fields

Abstract: Accumulated evidence identifies discernible gender gaps across many dimensions of professional academic careers including salaries, publication rates, journal placement, career progress, and academic service. Recent work in political science also reveals gender gaps in citations, with articles written by men citing work by other male scholars more often than work by female scholars. This study estimates the gender gap in citations across political science subfields and across methodological subfields within po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
361
1
18

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(400 citation statements)
references
References 53 publications
20
361
1
18
Order By: Relevance
“…However, that study found no evidence that citations per paper differed between men and women in ecology, consistent with two earlier studies of the ecology literature that failed to find gender differences in citations (Borsuk et al, ; Leimu & Koricheva, ). These results contrast with numerous studies in other disciplines, most of which show that papers authored by women are less well cited than papers authored by men, for example, across all sciences (Bendels, Müller, Brueggmann, & Groneberg, ; Larivière, Ni, Gingras, Cronin, & Sugimoto, ; Sugimoto, Lariviere, Ni, Gingras, & Cronin, ), in the social sciences (Carter, Smith, & Osteen, ; Dion, Sumner, & Mitchell, ), and in a variety of other disciplines (Tahamtan, Afshar, & Ahamdzadeh, ), though exceptions exist. Thus, as with studies of peer review, studies examining manuscript impact vary substantially in their conclusions.…”
Section: Introductioncontrasting
confidence: 87%
“…However, that study found no evidence that citations per paper differed between men and women in ecology, consistent with two earlier studies of the ecology literature that failed to find gender differences in citations (Borsuk et al, ; Leimu & Koricheva, ). These results contrast with numerous studies in other disciplines, most of which show that papers authored by women are less well cited than papers authored by men, for example, across all sciences (Bendels, Müller, Brueggmann, & Groneberg, ; Larivière, Ni, Gingras, Cronin, & Sugimoto, ; Sugimoto, Lariviere, Ni, Gingras, & Cronin, ), in the social sciences (Carter, Smith, & Osteen, ; Dion, Sumner, & Mitchell, ), and in a variety of other disciplines (Tahamtan, Afshar, & Ahamdzadeh, ), though exceptions exist. Thus, as with studies of peer review, studies examining manuscript impact vary substantially in their conclusions.…”
Section: Introductioncontrasting
confidence: 87%
“…For names that were not included in the SSA dataset, gender was assigned using Gender API (gender-api.com), a paid service that supports roughly 800,000 unique first names across 177 countries. We assigned 'man'('woman') to each author if their name had a probability greater than or equal to 0.70 of belonging to someone labeled as 'man'('woman') according to a given source (25). In the SSA dataset, man/woman labels correspond to the sex assigned to children at birth; in the Gender API dataset, man/woman labels correspond to a combination of sex assigned to children at birth and genders detected in social media profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Yet this formulation only measures the passive consequences of gendered citation behavior, rather than directly measuring the behavior itself. Instead, building on recent studies conducted in international relations and political science (25,29), we investigate the relationship between authors' gender and the gender make-up of their reference lists. Using this framework, we are able to quantify properties associated with authors serving as both objects and agents of undercitation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in neuroscience and other fields has identified a bias in citation practices such that papers from women and other minorities are under-cited relative to the number of such papers in the field (Maliniak et al, 2013, Caplar et al, 2017, Chakravartty et al, 2018, Thiem et al, 2018, Dion et al, 2018, Dworkin et al, 2020. Here we sought to proactively consider choosing references that reflect the diversity of the field in thought, form of contribution, gender, and other factors.…”
Section: Citation Gender Diversity Statementmentioning
confidence: 99%